Parcellation as a Stylistic Dominant Characteristic in the Novel Nigdina by Svetlana Velmar Janković - Mimović, Milica P. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The subject of this research is parcellation as a stylistic dominant characteristic in the novel “Nigdina” by Svetlana Velmar Janković, and also as the means of expression which is superior in regard to the other linguistic procedures. Considering the aim of syntactic-stylistic analysis in this paper, the examples were divided according to their syntactic functions identifying and interpreting syntactic structures that change word order, and simultaneously point out stylistic marking of the parcellated structure. The most frequent structures are the ones with parcellated positions of adjuncts. Adverbs and constructions with prepositions and case are comparably found in these syntactic positions. Moreover, the most frequent are adjuncts for the parcellation of syntactic position, then intonational and positional emphasis of apposition, and finally the parcellation of elements such as object, subject and an attributive.In conclusion, this procedure of making syntactic units independent, their frequency and superiority to the other stylistic procedures, contribute to the style of this novel, and point out parcellation as a dominant stylistic characteristic of this novel.